Cultural and Aesthetic Agency at the Intersection of Art and Economics - Gordon, Robert (Philosophy and Realistic Reflection, 2025)
An important element in understanding human life and history is how market forces and economic development relate to the creation and distribution of the significant artifacts of culture. The relationship between art and economics is important because commercial activity is a primary means by which humans sustain life amid the vicissitudes and dangers of the natural world. Understanding art and economics together sheds light on humanity’s need to establish norms of behavior, formulate rituals of cultural importance, and create institutions that help us work together in order to survive. This essay examines the relationship between economic life and cultural works found in both present-day and historical contexts. It investigates the extent to which aesthetic decisions are at the heart of economic life. Drawing upon Austrian-school economic thought, this article argues that the subjectivity of human agency is the connective idea linking the two spheres of human activity. In contemporary life, it has become clear that creativity is just as essential in business as it is in art. Historically, the artistic goal of creating beauty has had significant economic and commercial implications. Philosophically, concepts such as value and choice can have economic, aesthetic, and moral connotations. This article explores this network of economy, creativity, commerce, aesthetics, and morality with respect to some important artifacts from the art historical record.